Packaging closures and sealing systems / edited by Nigel Theobald. - Theobald, Nigel (Sheffield packaging technology ;, 2003)
These edited papers address the technologies relevant to packaging closures and sealing systems, structured by types of pack. Recent advances in closure and sealing technology mean that resealable packs can now be produced that are also able to signal whether tampering or prior opening has taken place.